# How do you solve 5( x - 2) - ( 4x + 4) = - 4?

Apr 5, 2018

$x = 10$

#### Explanation:

$5 \left(x - 2\right) - \left(4 x + 4\right) = - 4$

$5 x - 10 - 4 x - 4 = - 4$

$x - 14 = - 4$

$x = - 4 + 14$

$x = 10$

Apr 5, 2018

$x = 10$

Here's how I did it:

#### Explanation:

$5 \left(x - 2\right) - \left(4 x + 4\right) = - 4$

The first thing we want to do is use the distribute property. This means that we "distribute" or multiply the value outside of the parenthesis to everything inside it.

Let's look at $5 \left(x - 2\right)$. That means:
$5 \cdot x = 5 x$

$5 \cdot - 2 = - 10$

And when we combine them together we get $5 x - 10$.

Next, for $- \left(4 x + 4\right)$, we need to distribute the negative sign, so we get:
$- 4 x - 4$

So now the equation looks like this:
$5 x - 10 - 4 x - 4 = - 4$

Now we need to simplify and combine "like terms", so:
$x - 14 = - 4$

Now we add $14$ to both sides of the equation and get the value of $x$:
$x = 10$

Apr 5, 2018

$x = 10$

#### Explanation:

$5 \left(x - 2\right) - \left(4 x + 4\right) = - 4$

Open the brackets

$5 x - 10 - 4 x - 4 = - 4$

$5 x - 4 x - 10 - 4 = - 4$

$x - 14 = - 4$

Collect like terms

$x = 14 - 4$

$x = 10$ (Answer).